Komunikasi Antar Budaya Dalam Meningkatkan Harmoni Masyarakat Multikultural - La Ode Abdul Musawir; Abdul Rahmanb; Edy Samiel; Abdul Latif (CV. ITTC INDONESIA, 2025)
This study aims to determine Intercultural Communication in Improving Multicultural Community Harmony. The method used is literature analysis with the purpose of literature. Data collection is carried out through systematic searches of scientific literature on related articles, books, documents, and journals that discuss significantly related to the research theme, namely Intercultural Communication in Improving Multicultural Community Harmony. The technique used in this research is the Searching technique, which is taking references from the internet with the aim of helping to clarify and make it easier to review. The findings and subsequent discussion after the process of data collection and analysis, then the research provides a final conclusion as a closing. The results obtained that Multicultural societies make interactions with other communities that have different cultural differences.The differences that exist necessitate conflicts that occur because of differences so that it requires a common perception to unite these differences in order to create harmony in a multicultural society.Harmony that exists between multicultural communities is also based on effective communication between individuals with one another.In conducting communication in multicultural societies communication takes place verbally and non-verbally and cultural identity is inherent in the personalities of individuals who communicate. Multiculturalism in society not only reflects diversity, but also tests the extent to which individuals and groups are able to coexist harmoniously. The challenges that arise are often related to prejudice, discrimination, or unequal access to opportunities that should be enjoyed equally. The application of multiculturalism values in everyday life can be realised through social interactions that are respectful and open to differences. Cross-cultural activities such as the exchange of traditions, arts and languages can be an effective medium for strengthening relationships between community groups. This creates a deeper understanding of each other's backgrounds and reduces the potential for misunderstanding. In this way, multicultural societies not only coexist, but also thrive together in an atmosphere of peace and tolerance.Several strategies are implemented in order to recognise cultural diversity in communal life.Adaptation strategies can be implemented, such as acculturation, assimilation and separation, each of which has a different impact on intercultural relations.